The effectiveness of the thyroxine hormone in feed to improve growth performance efficiency and the survival rate of the cantang grouper (Epinephelus sp.) - Mahdaliana, Mahdaliana -; Salamah, Salamah (Acta Aquatica: Aquatic Sciences Journal, 2023)
This study aims to determine the effectiveness of the hormone thyroxine in feed to increase the efficiency of growth performance and revive the life of the cantang grouper (Epinephelus sp.). Something that can be done to achieve this goal is to provide the hormone thyroxine in fish feed to increase growth acceleration. This study used an experimental method using a non-factorial completely randomized design (CRD) with five treatments and three replications. The treatments in this study were: thyroxine hormone A (0 mg), B (6 mg), C (7 mg), D (8 mg), and E (9 mg). Parameters observed were: feed efficiency (ep), growth rate, feed conversion ratio (FCR), fish behavior, and survival. The results showed that fish behavior during rearing included fish movement, appetite, and fish skin color. The most active swimming fish were found in all treatments which were given feed containing the hormone thyroxine. The best feed efficiency (EP) value in treatment E was 76.29%. The value of the feed conversion ratio (FCR) in treatment E was 1.76%. The best growth was in treatment E in weight (2.88 cm) and length (36.85 cm). The best survival in treatments C and D was 98%. Water quality parameters during the study were temperature 27-280C, pH 7.0-7.9, Salinity 25-30 ppt, DO 5.9-6.9ppm, and Ammonia 0.0359-0.1946 ppm. The results of the observations showed that there were differences in fish-fed hormone-containing feed for 60 days and fish behavior. The fish looks more agile and the color is brighter.Keywords: Cantang Grouper; Feed; Growth; Survival; Thyroxine Hormone